Microkinetic Modeling of the Fischer–Tropsch Synthesis over Cobalt Catalysts. Issue 1 (6th October 2014) - Azadi, Pooya; Brownbridge, George; Kemp, Immanuel; Mosbach, Sebastian; Dennis, John S.; Kraft, Markus
Abstract We present a detailed microkinetic analysis of the Fischer–Tropsch synthesis on a Co/γ‐Al2O3 catalyst over the full range of syngas conversions. The experiments were performed in a Carberry spinning basket batch reactor at initial H2/CO ratios between 1.8 and 2.9, temperatures of 469 and 484 K, and initial pressures of 2 MPa. A reaction mechanism based on the H2‐assisted CO activation pathway, which comprises 128 elementary reactions with 85 free parameters, was proposed to explain the experimental results. Each of these elementary reactions belongs to one of the following reaction groups: adsorption–desorption, monomer formation, chain growth, hydrogenation–hydrogen abstraction, or water–gas shift. A two‐stage parameter estimation method, based on a quasi‐random global search followed by a gradient‐free local optimization, has been used to calculate the values of pre‐exponential factors and activation energies. The use of data obtained from batch experiments enabled an effective analysis of dominating reactions at different stages of syngas conversions.